2013
DOI: 10.1016/j.psychres.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use is associated with inattention in men and sleep quality in women with Attention-Deficit/Hyperactivity Disorder: A preliminary study

Abstract: The study examined the association between marijuana use, ADHD symptoms, and sleep quality in 56 men and 20 women with ADHD. Participants, ages 18-45, were assessed with the Assessment of Hyperactivity and Attention, drug use survey, and Pittsburgh Sleep Quality Index. Moderate to strong correlations were found between marijuana use and inattentive symptoms in men, and marijuana use and decreased sleep quality in women. Men and women with ADHD may use marijuana for different reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…At the same time, methylphenidate PCE use was also weakly associated with ADHD symptomatology, suggesting that, in a subset of students, PCE may approach self-medication [31] . Cannabis is another substance associated with self-medication of ADHD [32] . The relationship between use of stimulants for PCE, ADHD symptomatology, and cannabis use is complex and requires focused investigation.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, methylphenidate PCE use was also weakly associated with ADHD symptomatology, suggesting that, in a subset of students, PCE may approach self-medication [31] . Cannabis is another substance associated with self-medication of ADHD [32] . The relationship between use of stimulants for PCE, ADHD symptomatology, and cannabis use is complex and requires focused investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Ly and Gehricke 68 queried a group of 76 young adults (mean age = 26) with ADHD about their cannabis use, ADHD symptoms, and sleep quality. There was no control group of individuals without ADHD.…”
Section: Resultsmentioning
confidence: 99%
“…A study of teenagers also found that girls' sleep quality and hygiene was worse (Galland et al, 2017). Another study found a moderate to strong correlation between drug use and decreased sleep quality in women (Ly & Gehricke, 2013).…”
Section: Introductionmentioning
confidence: 98%